PELATIHAN DIFERENSIASI PRODK BERBASIS ZERO WASTE SOLUSI DAYA SAING DAN OMZET POKDAKAN NAMINASANG FARM & CO - Budiantoro, Harry; Santosa, Perdana Wahyu; Paramitra, Yuaniko; Zhafiraah, Nazma Riska; Oktavia, Dinda (Jurnal Abdi Insani, 2024)
Zero waste-based product differentiation training as a solution to improve the competitiveness of the Naminasang Farm & Co. fish farming group (POKDAKAN). Zero waste is an approach that optimizes the use of resources and reduces waste, resulting in environmentally friendly and more economically valuable products. This training aims to provide understanding and skills to POKDAKAN members in developing varied, innovative, and sustainable processed catfish products by utilizing waste from fish farming and processing. Through the zero waste approach, POKDAKAN Naminasang Farm & Co can create various new products such as animal feed from fish waste, organic fertilizer from fish farming waste, and healthy snacks from fish skin or bones. The results of this training are expected to improve operational efficiency, reduce production costs, and expand market share through sustainability-based product innovation. Thus, zero waste-based product differentiation is expected to be an effective strategy to improve the competitiveness of POKDAKAN Naminasang Farm & Co in local and global markets, as well as contribute to the circular economy and sustainable development.